Kontribusi Koping Religius Dalam Mengatasi Stres Pada Lansia Di UPT Pelayanan Sosial Tresna Werdha (PSTW) Blitar - Darwati, Yuli; Hafil, Ach. Shodiqil (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This research was conducted to determine the description of stress and religious coping of the elderly in dealing with stress at UPT PTSW Blitar along with their contribution in overcoming stress in the elderly at UPT PTSW Blitar. This research is a descriptive qualitative research. Data collection was carried out by observation and in-depth interviews with 11 elderly people and 5 employees at UPT PSTW Blitar. .The research results showed that all subjects experienced stress, both mild and severe. The causal factors vary, including physical and psychological factors originating from family, friends and regulations at UPT PSTW. Apart from that, all subjects used religious coping to deal with the stress they experienced, but with different strategies. Apart from religious coping, the elderly also developed other coping strategies, namely problem focused coping and other forms of emotion coping such as diversion and seeking social support. The religious coping of the elderly at UPT PSTW also varies, there are high, medium, low and very low in terms of the number of strategies used. Religious coping together with problem focused coping strategies and other forms of emotion focused coping can reduce stress in the elderly. Ten subjects felt that life was more comfortable and happier with lower levels of stress compared to when they initially entered UPT PSTW. Meanwhile, 1 subject did not experience a comfortable and happy life, on the contrary, he was in a condition of severe stress